Cyberculture networks in the literature from 2019 to 2022 - Francisco Espinoza Morales; Cruz García Lirios (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
Gross Similarly , cyberculture refers to a scenario of intellectual capital, which is an intangible asset for organizations focused on the management, production and transfer of knowledge. In this sense, the usefulness and ease of use of information technologies presuppose computational skills, but these entail risks and stigmas that inhibit the climate of relationships, support and innovation. Therefore, the establishment of a model for the study of organizational cyberculture around knowledge innovation is the objective of this work. A documentary study was carried out with a selection of sources indexed to national repositories in order to make a model for the study of cyberculture more complex. Lines of research concerning the amplification of repositories, techniques and theories around the amplification of the model are noted.